Didactic strategy to develop the skill “Identify” in medical students - Tatiana de la Caridad Gómez-Lloga; Yuray Agustina Franco-de la Yglesia; Isleny Mercedes Ramírez-Pelegrín; Mailiza Collado-Montes de Oca (Revista Información Científica, 2021)
Introduction: look for new routes to develop logical skills in students of Health Higher Education it’s a social demand in Cuba, focused directly on the skill “Identify” in medical students.